2018
DOI: 10.1186/s12864-018-5100-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genome analysis provides deep insights into Aeromonas hydrophila taxonomy and virulence-related factors

Abstract: BackgroundAeromonas hydrophila is a potential zoonotic pathogen and primary fish pathogen. With overlapping characteristics, multiple isolates are often mislabelled and misclassified. Moreover, the potential pathogenic factors among the publicly available genomes in A. hydrophila strains of different origins have not yet been investigated.ResultsTo identify the valid strains of A. hydrophila and their pathogenic factors, we performed a pan-genomic study. It revealed that there were 13 mislabelled strains and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 65 publications
2
21
0
Order By: Relevance
“…Preliminary analysis detected virulence factors similar to the genes of the type III secretion system in the seabass’ GIs as described elsewhere [66]. In addition, the analogy of prophages per genome detected in the current study, although not intact, is mentioned before in another species of the genus, A hydrophila [54,67,68]. Prophage genes are widely distributed within the aeromonads [69,70], but in the course of evolution there is a constant process of losing and acquiring such genetic material.…”
Section: Discussionsupporting
confidence: 59%
“…Preliminary analysis detected virulence factors similar to the genes of the type III secretion system in the seabass’ GIs as described elsewhere [66]. In addition, the analogy of prophages per genome detected in the current study, although not intact, is mentioned before in another species of the genus, A hydrophila [54,67,68]. Prophage genes are widely distributed within the aeromonads [69,70], but in the course of evolution there is a constant process of losing and acquiring such genetic material.…”
Section: Discussionsupporting
confidence: 59%
“…were incorrectly labeled. Recently, different studies used the genomic indices to increase the correct identification of ambiguous Aeromonas strains, supporting the notion that these methods are essential in taxonomy [94][95][96].…”
Section: Genomicsmentioning
confidence: 78%
“…Recently, it was estimated that ∼18% of the organisms are misclassified in microbial genome databases 2 . This high rate of error led to investigation of misclassification of specific organisms, including Aeromonas 6 Fusobacterium 7 , and ultimately entire reference databases 2 . These studies found misclassified type strains, which calls into question the foundation of the taxonomy and inferred relatedness when population genomes are being used for epidemiological purposes, especially with rare organisms that are not well represented in the reference database.…”
Section: Introductionmentioning
confidence: 99%